Employee Perceptions and Intention to Leave Among Academic Staff in Public Universities in Kenya - Orwa, Atieno Carolyne; Muchibi , Wilbroda; Miroga , Julius (Human Resource and Leadership Journal, 2024)
Purpose: The specific objectives of the study included perceived organizational support, commitment, performance and perceived organizational support as predictors of intention to leave. Methodology: The descriptive survey research designs was adopted. The population consisted of all cadres of academic staff in the chosen three public universities in Western Kenya. Yamane’s (1967) formula was utilised in determining a sample size of 121 respondents. Purposive sampling technique was utilised in coming up with the sample. Questionnaires were used to obtain primary data for analysis. A pilot study was done on 5% of the sample and Cronbach’s alpha helped in testing reliability. Both face and content validity of the research instrument were checked. Descriptive and inferential statistics of frequencies, means and standard deviation and inferential technique were utilised to analyse quantitative data using SPSS. Findings: The results revealed that perceived organizational support had a negative significant relationship with intention to leave. Perceived commitment, performance and manager support were all positively related with intention to leave. Unique Contribution to Theory, Policy and Practice: The study recommends that universities should assess and improve employee perceptions if they want to influence them to stay longer with the firms.